Identification of a laccase gene family in the new lignin-degrading basidiomycete CECT 20197. - Mansur, M (1997)
A new lignin-degrading basidiomycete, strain I-62 (CECT 20197), isolated from decayed wood exhibited both a high dephenolization activity and decolorization capacity when tested on effluents from the sugar cane by-product fermentation industry. It has been classified as a member of the Polyporaceae family. The major ligninolytic activity detected in culture supernatants of basidiomycete I-62 was a phenoloxidase (laccase), in conjunction with small amounts of manganese peroxidase. No lignin peroxidase was detected. Laccase activity was produced in either defined or complete media. Addition of veratryl alcohol as the inducer, in defined medium, enhanced laccase production 10-fold. The use of fructose instead of glucose as a carbon source resulted in a 100-fold increase in laccase specific activity. Native isoelectrofocusing gels stained with guaiacol revealed the presence of at least seven laccase isozymes, with the most intense band being detected at pI 3. Southern hybridization analysis indicated the presence of a laccase gene family in strain I-62. Three different genes coding for phenoloxidases, lcc1, lcc2, and lcc3, were cloned and characterized. The high degree of homology between laccases from strain I-62 and laccases from Trametes species suggests a phylogenetic proximity between this new isolated fungus and the genus Trametes.